Profitability of foreign banks in Central and Eastern Europe: does the entry model matter? - Olena Havrylchyk; Emilia Jurzyk (Bank of Finland, Institute for Economies in Transition (BOFIT), 2006)
Using data for 265 banks in Central and Eastern European Countries for the period of 1995-2003, this paper analyses the differences in profitability between domestic and foreign banks.We show that foreign banks, especially greenfield institutions, earn higher profits than domestic banks.However, this effect is acquired rather than inherited, since there is evidence that foreign banks tend to take over less profitable institutions.Profits of foreign banks in CEECs also exceed profits of their parent banks, explaining the reasons for their entry.Further, we study benefits and costs of foreign ownership by analyzing determinants of profitability for domestic, takeover, and greenfield banks.Profits of foreign banks are less affected by macroeconomic conditions in their host countries.However, greenfield banks are sensitive to the situation of their parent banks.Only domestic banks enjoy higher profits in more concentrated banking markets, whereas takeover banks suffer from diseconomies of scale due to the fact that they acquired large institutions.
URN:NBN:fi:bof-201408072157
Keywords: G15; G21; F36; 330; foreign banks; bank profits; multinational banking; transition economies